Synthesis and Characterization of Some Metals Complexes with New Heterocyclic Azo Dye Ligand 2-[2ــ-(Benzimidazolyl) azo]-5-DimethylaminoBenzoic Acid - Faiq F. Karam (Journal of Global Pharma Technology, 2016)
A new chelating imidazolylazo groups were synthesis. New ligand of azo dye 2-[2ــ- (benzimidazolyl) azo]-5 -dimethyl amino benzoicacid (BIABA) have been synthesized by diazotization in alkaline alcoholic solution. Complexes of this ligand were prepared with a series of metallic ions Cu (II), Co (III), Ni (II). These complexes were examined using UV-Vis spectroscopy, the surface nature, morphology and elemental composition of individual novel (BIABA) ligand particles were characterized using Field Emission Scanning Electron Microscope (FE-SEM) coupled with an Energy Dispersive X-ray system (EDX). The structures of the synthesized dyes were determined by analysis of their Mass spectrum, Fourier-transform infrared (FTIR), 1H NMR. The physical properties of ligand have been studied via check its melting point.Keywords: Azo dye; Benzimidazol; Benzoic acid; 1H NMR; FESEM; X-ray system.